Rights of Restitution to Child Victims Under Law No. 35 of 2014 Concerning Child Protection - Hasibuan, Lidya Rahmadani; Lubis, Syaravina (Mahadi: Indonesia Journal of Law, 2024)
Restitution is the compensation paid by a perpetrator, as determined by a court with a final legal decision, to cover the material and/or immaterial losses suffered by the victim or their heirs. In cases involving child victims, restitution becomes obligatory for the perpetrator to compensate the victim for their losses. This demonstrates the perpetrator's responsibility for actions that have harmed the victim, their family, or heirs, in accordance with Article 71 D Paragraph (2) of Law Number 35 of 2014, which amends Law number 23 of 2002 concerning Child Protection. Restitution, as a form of compensation for victims of crimes, aligns with the Principle of Restoration to its Original Condition (restitutio in integrum), aiming to restore victims to their state before the crime, although complete restoration may not be possible. It emphasizes a holistic recovery approach, addressing various aspects resulting from the crime's consequences. Through restitution, victims can recover their freedom, legal rights, social status, family life, citizenship, residence, employment, and assets. The research will be conducted at the Belawan Police, Medan LPSK, and Bagan Deli Belawan Village.